Development of Civil Servants in Public Service at the West Kairatu Sub-district Office, West Seram Regency - Iriane Sosiawaty Ponto; Jeanly Waisapy; Zul Fadli (Jurnal Manajemen Pelayanan Publik, 2023)
This study analyzes the development of the Civil Servant Apparatus (ASN) in public service at the West Kairatu Sub-District Office, West Seram Regency. The research method is quantitative, utilizing a questionnaire instrument to collect data from the ASN at the office. The method of data analysis is quantitatively descriptive, and the research results are presented concisely for easy comprehension. The main focus includes work discipline, career development for ASN, and the application of ethical codes in public service. Work discipline is measured through attendance, strict rules aspect, and responsibility. The analysis results indicate "poor" attendance, while adherence to rules and responsibility are rated as "very good." A civil servant's career development is measured by participation in technical training and leadership training. Participation in technical training is rated as good, while participation in leadership training is rated as “poor." Furthermore, the application of ethical codes is rated as “good." Recommendations encompass effective training programs and attendance management, encouraging active participation in leadership training, as well as periodic ethical code socialization and monitoring. These findings guide enhancing the development of civil servants and public service.